Paramount urdu silsila: karwan e urdu class 2 - Ali, Akbar (Paramount books Karachi, 2021)
"Paramount Urdu Silsila: Karwan-e-Urdu" is a comprehensive series designed to promote and teach the Urdu language through various engaging methods. It focuses on enhancing language skills, including reading, writing, and speaking, while also exploring the rich cultural and literary heritage of Urdu.